MEDITS-based information on the deep water red shrimps Aristaeomorpha foliacea and Aristeus antennatus (Crustacea: Decapoda: Aristeidae) - Cau, Angelo; Carbonell, Aina; Follesa, Maria Cristina; Mannini, Alessandro; Orsi Relini, Lidia; Politou, Chrissi Yianna; Ragonese, Sergio; Rinelli, Paola (Scientia Marina, 2002)
The application of statistical models on a time series of data arising from the MEDITS International Trawl Survey, an experimental demersal resources survey carried out during six years (1994-1999) in the same season of the year (late spring - early summer) using the same fishing gear in a large part of the Mediterranean, has allowed for a study to compare, for the first time, the space-time distribution, abundance, and size structure of the two Aristeids Aristaeomorpha foliacea and Aristeus antennatus throughout most of the Mediterranean Sea. This research has shown a large variability among the six reference areas, that were arbitrarily defined within the basin. In particular the two shrimps do not seem to present any correlation or yield continuity in the years. The same lack of homogeneity was also observed in the time trend of the abundances and frequencies of each of the two species. These data seem to confirm the intrinsic variability of the species, the cause of which is still unknown and undocumented. Nevertheless, a longitudinal gradient of catches has been observed where A. antennatus is more abundant in the west and A. foliacea in the east of the basin.